Composite media with reduced write temperature for heat assisted magnetic recording - N.A. Natekar; W. Tipcharoen; R.H. Victora (My University, 2019)
A major issue plaguing Heat Assisted Magnetic Recording (HAMR) is the high writing (Twrite) and peak heat spot temperatures (Tpeak). To counter this, a low temperature thermal exchange coupled composite (ECC) media with reduced write temperature relative to previous high temperature thermal ECC media is introduced. The FePt Tc is reduced from 700 K to 500 K, and the write layer Tc is reduced from 900 K to 600 K. Optimizations for Ms and Ku of the write layer generate values of Ms = 700 emu/cm3 and Ku = 1.0 × 107 erg/cm3 at 300 K. Switching Probability Distribution (SPD) calculations with lowered Tpeak = 650 K indicate Twrite = 487 K. This indicates a Twrite reduction by 34% as compared to the previous write temperature of 738 K for the high temperature thermal ECC media. Examining the FWHM of the SPD under 0% and 3% Tc variation indicates a noise reduction of ∼20% relative to single layer high Tc FePt media, and a much larger reduction relative to low Tc FePt media. The jitter values at lowered Tc approach the ideal value set by the grain size in the absence of any Tc and Ku variation. Simulations with uncorrelated and correlated Tc and Ku variations in the write and FePt layer generate similar results. Reduction of FePt Tc may reduce the anisotropy relative to its undoped value: reduction of anisotropy by 33% is found to adversely affect the SPD by only 3–4%, but has a larger impact on jitter. These results help establish the usefulness of a low temperature thermal exchange coupled composite media for HAMR.
Keywords: Heat-assisted magnetic recording; Magnetic properties of thin films